PENGARUH KEPEMIMPINAN TERHADAP PEGAWAI PADA KANTOR INSPEKTORAT KABUPATEN NIAS SELATAN - Sri Sartika Maduwu (Universitas Nias Raya, 2022)
The prupose of this study was to determine the influence of leadership on employe performance at the Inspectorate Office Of South Nias Regency. The type of research used is associtive quantitative. Souerces of data are all employees, with the population and sampel ini this study as many as 34 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is simple resgression analysis. The result showed that the tcont 7,227 > ttable 1,694. From this study, it can be councluded that there is an influence of leadership on employee performance at the south Nias District Inspectorate Office. The suggestion of this research is to improve the performance off employees as well as leader at the Sout Nias Regrency Inspectorate Office, they must really continue to improve employee performance even better and pay attention to he best, Because the existing leadership will have an effect on employe performance